Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for the Management of Patients With Positional Plagiocephaly: Executive Summary. Issue 5 (November 2016) - Flannery, Ann Marie; Tamber, Mandeep S.; Mazzola, Catherine; Klimo, Paul; Baird, Lissa C.; Tyagi, Rachana; Bauer, David F.; Beier, Alexandra; Durham, Susan; Lin, Alexander Y.; McClung-Smith, Catherine; Mitchell, Laura; et al.
Abstract : BACKGROUND: Positional plagiocephaly is a common problem seen by pediatricians, pediatric neurologists, and pediatric neurosurgeons. OBJECTIVE: To create evidence-based guidelines for the treatment of pediatric positional plagiocephaly. METHODS: This guideline was prepared by the Plagiocephaly Guideline Task Force, a multidisciplinary team made up of physician volunteers (clinical experts), medical librarians, and clinical guidelines specialists. The task force conducted a series of systematic literature searches of PubMed and the Cochrane Library, according to standard protocols for each topic addressed in subsequent chapters of this guideline. RESULTS: The systematic literature searches returned 396 abstracts relative to the 4 main topics addressed in this guideline. The results were analyzed and are described in detail in each subsequent chapter included in this guideline. CONCLUSION: Evidence-based guidelines for the management of infants with positional plagiocephaly will help practitioners manage this common disorder. The full guidelines documents can be located athttps://www.cns.org/guidelines/guidelines-management-patients-positional-plagiocephaly .